A conceptual limbo of genocide: Russian rhetoric, mass atrocities in Ukraine, and the current definition's limits. Issue 2 (3rd July 2022) - Dudko, Oksana
ABSTRACT: The presence of multiple, semantically opposed usages of the term "genocide" not only poses a challenge for legally defining Russia's atrocities in Ukraine, but also exemplifies the constraints of international law in dealing with mass civilian destruction in the twenty-first century. Indeed, despite widespread evidence of Russia's genocidal behaviour, few scholars and lawyers believe it would be legally possible to prove Russia's genocide in Ukraine. Nonetheless, given the powerful public image of genocide as the "crime of crimes, " political usage of the term by politicians, activists, and the general public has intensified since the beginning of Russia's 2022 invasion with the hope of attracting global attention to (and ceasing) Russia's atrocities. This paper provides some preliminary observations on how and why the concept of genocide has proven to be effective in fuelling civilian destruction rather than preventing it during the invasion. It first traces how Russia's controversial, two-pronged rhetoric of genocide has evolved over the initial months of the invasion. It then examines Russia's atrocities and the difficulties of classifying them as genocide.